Awareness and desirability of antenatal attendees about analgesia during childbirth in a university teaching hospital in southern Nigeria - Abasiattai, Aniekan Monday; Olatunbosun, Olujimi; Edubio, Mark Nyong (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Labour pain is among the most severe pains humans experience and when unrelieved, is associated with adverse maternal and foetal effects. Methods: Structured questionnaires were administered to 268 consenting parous women in the antenatal clinic of the University of Uyo Teaching Hospital, Nigeria over a 4-months period. Results: The majority of the respondents were between 25-34 years (84.0%), and were well educated (64.4%). About half (59.7%) of the respondents did not know that pain free labour was possible, while only 6.7% of the women had pain relief in their last delivery. The majority (81.4%) desired pain relief during their next delivery. Books (35.1%) and friends/relatives (32.4%) were the most common sources of information on pain relief in labour. Perception of pain was positively associated with the educational level of the women (P=0.013).There was also a significant association between ethnicity and desirability for labour pain relief. Conclusions: The practice of obstetric analgesia in labour is far from optimal in our center. The need to create awareness about pain relief in labour and its importance specifically among our antenatal clients cannot be overemphasized.